Driving Strategic Industries with Factors of Production: China’s Xinjiang and Mongolia’s Western Region (Mongolian Journal of International Affairs, 2025)
Xinjiang Autonomous Region of the People’s Republic of China (Xinjiang) has established an industrial structure focused on the heavy industry by taking the advantage of having vast natural resource reserves located within the region. This has become a vital base to the country for the development of petroleum, natural gas, coal, chemicals, fuel processing, non-ferrous metals, and non-metallic mineral products. However, Xinjiang has been facing inevitable challenges of embarking on industrial reforms and developing its competitive advantages largely because of the weakened primary industrial factors and the reinforced green development requirements. As for Mongolia’s Western Region, which borders Xinjiang, it has the advantages of natural resources, historical and cultural heritage, but it is still in the early stage of industrial development, relying on agricultural and raw material exports, and facing challenges such as a shortage of infrastructure and labor resources. First part of this paper, by taking the theory of factors of production, briefly explains how to create a competitive advantage within the industry sector and develop strategic industries, while the second part refers the current conditions of the Xinjiang’s industrial development, the challenges encountered, and the ways being used to resolve such challenges. Finally, the paper outlines some issues for the industrial development of Mongolia’s Western Region.